Optimal Relay Node Selection Using Multi-objective based Lion Optimization Algorithm for Multiuser Cooperative Communication Network - Anand Ranjan, O.P. Singh, G.R. Mishra, Himanshu Katiyar (International Journal of Advanced Science and Technology, 2020)
In recent years, cooperative relaying technique is considered as an important technique for mesh network, Wireless Sensor Network (WSN), Ad-hoc network and Cellular network. In this cooperative communication network, relay nodes are allocated between source and destination for facilitating the data transmission. Still the selection of relay node is one of the main challenges for improving the performance of cooperative communication network. So, in this paper, a Multi-objective based Lion Optimization Algorithm (LOA) is presented for multiuser cooperative communication network. For optimal relay node selection, multi-objective functions based on Signal to Noise Ratio (SNR), channel gain in addition to power consumption are defined in this approach. With these objective functions, LOA algorithm executes and selects an optimal relay node. The simulation result shows the developed approach efficiency evaluation regarding SNR, Throughput, Delay, lifetime of the network and Energy consumption. Keywords: Cooperative communication network, Relay node selection, Multi-objective based Lion optimization algorithm, power efficiency.